Learning Interest and Academic Success: Investigating the Moderating Role of Infrastructure at Udayana University's Management Program - Ni Putu Metya Juniari; Ni Wayan Rusma Wardani (The Journal of Management, Digital Business, and Entrepreneurship, 2024)
This study aims to examine the effect of learning interest on the Cumulative Achievement Index (GPA) of students of the Management Study Program at Udayana University, with campus infrastructure as a moderating variable. This study uses a quantitative approach and explanatory design to identify causal relationships between variables. The independent variable in this study is learning interest, the dependent variable is GPA, and the moderating variable is campus infrastructure. The population of the study was all active students of the Undergraduate Management Study Program at Udayana University, totaling 41 people, with a sampling technique using total sampling. Data were collected through a closed questionnaire based on a Likert scale and tested using a moderated regression analysis technique (MRA) with the help of statistical software. The results of the analysis show that learning interest has a positive and significant effect on students' GPA. Furthermore, campus infrastructure does not moderate the relationship, meaning that students' perceptions of campus infrastructure and facilities do not increase the influence of learning interest on academic achievement. The implications of this study indicate the importance of strengthening students' learning interest through a participatory pedagogical approach to create a conducive learning environment. These findings are expected to be a reference for policy makers in higher education environments in formulating strategies to improve the quality of education based on a holistic approach between internal and external aspects of students.